Reasons for failure of breast-feeding counselling: mothers' perspectives in Bangladesh. - Haider, R. (World Health Organization, 1997)
During the hospitalization in the Dhaka hospital of the international Centre for Diarrhoeal Disease Research, Bangladesh, of a group of partially breast-fed infants aged 1-12 weeks who had been admitted with acute diarrhoea, their mothers were individually counselled by breast-feeding counsellors to start exclusive breast-feeding. The counselling was repeated 1 week later at home, and the women's infant-feeding practices were evaluated 2 weeks after their infants had been discharged from hospital. A total of 25% of the mothers failed to breast-feed exclusively despite having been counselled. The case studies of these mothers illustrate that although they generally complained about having "insufficient breast milk" various factors such as domineering grandmothers, lack of financial support by their husbands, too much housework, or disinterest contributed to their failure to breast-feed exclusively. While family support is essential for all lactating mothers, women with familial or financial problems require special attention and extra counselling sessions so that they can be helped to identify how to achieve and sustain exclusive breast-feeding.